Pengaruh Kualitas Pelayanan dan Fasilitas terhadap Loyalitas Pelanggan Menggunakan Jasa Bengkel Mobil pada PT. Capella Daihatsu Medan Gatsu 2 - Kelvin Siahaan; Ahmad Rafiki (RIGGS: Journal of Artificial Intelligence and Digital Business, 2026)
This study aims to analyze the effect of service quality and facilities on customer loyalty at PT. Capella Daihatsu Medan Gatsu 2. Increasingly fierce competition in the automotive service industry requires companies to improve service quality and facilities in order to maintain customer loyalty. The population of this study consists of customers who have used the service more than once. The sample was determined using the Slovin formula, consisting of 99 respondents. Data were collected through questionnaires and analyzed using SPSS version 27. The results showed that service quality had a positive and significant effect on customer loyalty with a t-value of 3.834, which was greater than the t-table value of 1.985, and a significance value of 0.001, which was less than 0.05. Facilities also have a positive and significant effect on customer loyalty with a t-value of 3.493, which is greater than the t-table value of 1.985, and a significance value of 0.001, which is less than 0.05. Simultaneously, service quality and facilities have a significant effect on customer loyalty with a calculated F value of 92.428, which is greater than the F table value of 3.09, and a significance value of 0.001, which is less than 0.05. The coefficient of determination test results show an Adjusted R Square value of 0.651, which means that 65.1% of the variation in customer loyalty can be explained by service quality and facilities, while the remaining 34.9% is influenced by other factors outside this study. Adjust to the abstract writing style.